Upaya Pencegahan dan Penanganan Bullying melalui Edukasi Budaya Positif di SMPN 1 Wonosari - Suking, Arifin; Mas, Sitti Roskina; Sulkifly, Sulkifly; Akadji, Fachrudin; Tolinggi, Margaretha; Yolanda, Sri Mei; Gani, Wawan Iskandar; Sarapia, Nurmila (Universitas Negeri Gorontalo, 2025)
Bullying is a problem that frequently occurs in school environments and has negative impacts on students’ psychological, social, and academic development. This condition highlights the importance of strengthening a positive school culture as a preventive effort to create a safe and comfortable learning environment. This activity was a community service program aimed at increasing students’ knowledge, understanding, and awareness of the forms, impacts, and prevention strategies of bullying through the reinforcement of positive culture at SMP Negeri 1 Wonosari, Boalemo Regency. The community service methods included interactive lectures, discussions, and educational video screenings involving 49 junior high school students as participants. The evaluation was conducted using simple indicators, including observation of participant engagement, question-and-answer sessions, and individual summary assignments to assess improvements in understanding. The results showed that approximately 85% of participants were actively involved in discussions, 78% of students were able to clearly explain bullying concepts and prevention strategies, and a positive change in students’ attitudes toward rejecting bullying behavior was observed. Overall, this community service activity plays an important role in enhancing students’ awareness and participation in building a safe, inclusive, and positive school culture as a strategic approach to bullying prevention.